Development of Pinus Pengger Forest Geotourism in The Mangunan Protected Forest Area Bantul Regency, Special Region of Yogyakarta - Ghalbi Mahendra Putra; Pramudya Bagas Utama; Badarudin Aswat Tutupoho; Nugraha Alfuqril (International Journal of Geotourism Science and Development, 2022)
A Forests have many benefits, is as a provider of environmental services for geotourism. The development of geotourism in forest areas is Pinus Pengger, Bantul Regency. The development of Pinus Pengger geotourism must be evident and directed according to the principle of using sustainable geotourism environmental services. The Research was conducted to determine a sustainable geotourism management strategy beneficial and sustainable. The analysis uses the SWOT method, the data support of surveys, and information from various literature. The results of the research show that Pinus Pengger geotourism has a landscaping potential that supports it to be developed. The Pinus Pengger geotourism development strategy comprehensively prioritizes the preservation of the forest environment and involves the community. Sustainable geotourism development can ensure the sustainability of forests and still benefit the community.